Novel Terpineol-Based Silver Nanoparticle Ink with High Stability for Inkjet Printing - Aleksandrs Novikovs; Tamara Tsebriienko; Annamarija Trausa; Anete Berzina; George Chikvaidze; Dmitry Bocharov; Mohammad Yusuf Mulla; Juris Purans; Boris Polyakov (Nanomaterials, 2025)
This study presents a novel silver nanoparticle ink formulation designed for inkjet printing applications using terpineol as an eco-friendly solvent and butylamine as a stabilizer to ensure stability, high conductivity, and compatibility with inkjet technology. Silver nanoparticles were synthesized using a modified one-pot method in the presence of highly effective stabilizers and surface modifiers such as oleic acid and oleylamine, resulting in uniform particles of less than 10 nm in size, which were then dispersed in a mixture of terpineol and butylamine. The resulting ink demonstrated exceptional stability over 85 days, maintaining optimal rheological properties for inkjet printing. The ink exhibited a perfect jetting performance. We were able to obtain silver conductive patterns reaching 81% of bulk silver conductivity. These results highlight the ink’s promise for scalable, sustainable manufacturing, combining environmental advantages with high-performance functionality.